Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (IDS, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.
Accepted: 2022-04-25T10:25:54Z Publisher: Institute of Development Studies